Multifunctional integration of breakwaters: Taking ecological protection and restoration as an example - Xia Yuyang (E3S Web of Conferences)
This paper focuses on breakwater design and development in coastal and ecosystem protection contexts. It investigates traditional breakwaters’ negative impacts on the marine ecosystem, like disrupting sediment transport and reducing water exchange, causing sediment accumulation and pollution. Current research deficiencies are identified, including a lack of long-term ecological impact studies, insufficient research on sustainable materials, and incomplete impact assessments on local communities and the economy. The review investigates breakwater-ecosystem integration in three aspects. For water exchange, it discusses culverts and permeable breakwaters, considering their effectiveness and factors like location and size. Eco-friendly materials like ecological concrete and its benefits for organisms and the environment are presented, along with other recycled materials’ economic advantages. The importance of providing biological habitats to increase biodiversity is also investigated. Case studies illustrate these concepts. However, current breakwater design and research have limitations. Future research should focus on ecological functions, compensation and restoration strategies, sustainable materials, and impact assessments. International cooperation should be enhanced for more effective breakwater design and sustainable coastal development.